Formulation and In-Vitro Evaluation of Carvedilol Buccal Films Using HPMC E15 and Sago Starch as Polymer - Krishnaveni Manubolu; Mohammad Amisha Sulthana; K. Harinadha Baba (International Journal of Pharma and Bio Sciences, 2024)
The study aimed to formulate and evaluate carvedilol-loaded buccal films using Sago starch and HPMC E15 as polymers. Carvedilol (Dose-3.125-25 mg) has α1-, β1- and β2-adrenergic blocker activity with other activities like antioxidant, calcium antagonist blocking, and smooth muscle proliferation action. Its oral bioavailability is 25-35% because of first-pass metabolism. Hence the main research objective is to formulate a buccal mucoadhesive dosage form for Carvedilol in the form of buccal Films by using two different semi-synthetic and natural polymers, Hydroxy Propyl Methyl Cellulose HPMC E15 and Sago Starch, to overcome the hepatic metabolism, reduce dosing frequency, low bioavailability, and to give controlled release of a drug and to improve patients’ compliance. The FTIR method revealed no interaction between carvedilol or any other polymers. Carvedilol buccal films were prepared using HPMC E15 and Sago starch solvent casting. The films were evaluated for thickness uniformity, folding endurance, weight uniformity, and content uniformity, swelling index, mucoadhesive strength, surface pH, kinetic, in-vitro, and Ex-vivo permeation studies. The thickness and weight uniformity of the prepared buccal films were found to be in a satisfactory range, the films have good folding-endurance over 300 folds, and the surface pH of the films ranged from 6.4-7 neutral pH. The drug content of the films was found to be uniform. The swelling index of buccal films was higher in the HPMC E15 films than in sago starch films. All buccal films have more than 7 hours of in-vitro residence time. The permeation studies were performed using goat buccal mucosa in a modified Franz diffusion cell for carvedilol-loaded buccal films in phosphate buffer for 8 hours, showing 95.04% permeation. In-vitro release studies were performed for carvedilolloaded buccal films in a phosphate buffer (6.8 pH) solution. The optimized film (S3) exhibited drug release 98.96% in 8 hours. Data from in-vitro release and ex-vivo permeation studies of films were fitted into kinetic models (Higuchi, Korsmeyer-Peppas models) to explain release profiles. The optimized formulations showed zero-order release followed by first-order and diffusion mechanisms (Higuchi). Thus, the prepared formulation of the carvedilol-loaded buccal film of sago starch and HPMC E15 can provide a controlled release and overcome the fast-pass metabolism of the drug.